EVALUASI KEBIJAKAN PEMBANGUNAN PUSKESMAS PEMBANTU DI PROPINSI KALIMANTAN TENGAH - Deni Kurniadi Sunjaya, Kus Winarno Mubasysyir Hasanbasri (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: The objective of health development is improvingcommunity health status through increasing public access tohealth services. One of strategy is by supporting facilities forhealth service by developing auxiliary health center for allremote district at Central Kalimantan Province. CentralKalimantan Province with 1,9 million of population, consistedof 14 district, 1348 villages, 805 auxiliary health center. It meansthat only 59% village have facilities for health service such asauxiliary health center.Objectives: This research aimed to know how formulationprocess and implementation of policy of developing auxiliaryhealth center by using provincial funds.Method: It was descriptive case study using mainly methodqualitative designed by semi structured in-depth interview anddocument study. Research subject is stakeholder at levelprovince and chosen district. This research executed inProvince Public Health Service of Central Kalimantan and onechosen district.Result: Development of secondary health center in CentralKalimantan Province is the realization of Central KalimantanProvince local decree number 12 and 13 year 2005 fulfilmenton RPJPD and RPJMD. Initially, the budgeting concept wasplanned by Tugas Pembantuan mechanism, but this mechanismwas not agreed. This scheme was a top down program fromprovince government. Problems occurred in the implementationare 1). Bad monitoring, 2). Lack of reporting by developer, 3).Remote location of, 4). Varieties in cost of production, 5).Shortage health care workforce, 6). Equipments unmatchedthe need of health care provider. Evaluation is executed, butonly concerning physical progress problem. In the meantime,there was increased allocation of DAK fund in each district.Conclusion: Development of auxiliary health center in CentralKalimantan Province which funded by province fund, is notrequired by district. There was no agenda surroundingdevelopment of auxiliary health center. The role of stakeholderin compilation of agenda setting for this policy was only anormative role.Keyword. Auxiliary health center policy, evaluation,decentralization, central Kalimantan